A Longitudinal Study of Spirituality, Character Strengths, Subjective Well-Being, and Prosociality in Middle School Adolescents - Kor, Ariel; Pirutinsky, Steven; Mikulincer, Mario; Shoshani, Anat; Miller, Lisa (Frontiers in Psychology, 2019)
Using data from 1,352 middle-school Israeli adolescents, the current study examines the interface of spirituality and character strengths and its longitudinal contribution to subjective well-being and prosociality. Participants were approached three times over a 14-months period and completed measures of character strengths, spirituality, subjective well-being (positive emotions, life satisfaction), and prosociality. Findings revealed a fourth-factor structure of character strengths that included the typical tripartite classification of intrapersonal, interpersonal, and intellectual strengths together with spirituality emerging as a statistically autonomous factor. Spirituality was stable over time and contributed to higher subjective well-being and prosociality both cross-sectionally and longitudinally. Discussion focuses on spirituality as a fundamental character strength and an important aspect of positive development.